Politico-Economic Determinants of Tort Reforms in Medical Malpractice - Ulrich Matter; Alois Stutzer (University of Basel, Center of Business and Economics (WWZ), 2015)
The U.S. tort system has experienced various reforms during the last three decades. While there is a broad literature on the consequences of these reforms, very little is known about their determinants. In this study, we investigate the politico-economic forces that were driving the reform process across U.S. states. We focus on five types of medical malpractice tort reform and apply semi-parametric proportional hazards models to assess the factors that are related to reform enactments. We find, first, that a higher fraction of Republicans in a state legislature as well as a Republican governor are the major drivers of medical malpractice tort reforms. Second, we find that a higher fraction of women in a state legislature is associated with reforms being deferred. This finding is corroborated by micro-evidence on female legislators' voting behavior on medical malpractice tort reforms, and it is consistent with the notion that women are disproportionally aggrieved by such reforms.
Keywords: D72; K13; 330; Tort reform; tort law; medical malpractice; rent-seeking; legislatures; women in politics